An Analysis Of Factors Influencing The Development Of Speaking Skills For Non-Native Speakers Of English - Kholmurodova Dilnoza Kholmurod Kizi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the English as a Foreign Language (EFL) pedagogy environment, how to increase speaking competence and confidence for undergraduate students tends to be a crucial question among instructors. This paper aims at establishing the need to focus on the factors affecting on language learners’ English speaking skill. The findings indicated that confidence, creativity of topics, and speaking competence were the key aspects of improvement when speaking to the audience.